Self-Regulation of Learning and Academic Self-Efficacy: contributions to the educational context (Research, Society and Development, 2020)
The Social Cognitive Theory starts from the premise that we, subjects, interact with the environment in which we live, receiving influences bidirectionally - context and individual. In this way, the subjects are able to operationalize changes in the course of their own actions, thoughts and emotions. From a sociocognitive perspective, the concepts of self-regulation and self-efficacy are fundamental in understanding the processes involved in the learning of individuals and, therefore, are essential for understanding the factors related to the training of university students. Thus, this study aims to discuss the concepts of self-regulation and academic self-efficacy and their contributions to understanding the cognitive, metacognitive, behavioral and motivational processes related to the educational context. For this, bibliographic research was carried out, with a narrative focus, from national and international authors, such as Albert Bandura (1986, 1991, 2003, 2008); Zimmerman (2000); Pajares, Olaz (2008); Azzi (2012); Mazotti (2014); Ramos (2015); Silva (2019), among others. It is understood that the Cognitive Social Theory has important concepts in the process of developing self-regulation and self-efficacy beliefs for understanding how individuals observe, judge and act on their own behaviors and how they structure, monitor and evaluate their learning.